NEUROPHARMACOLOGICAL PROFILE OF AQUEOUS EXTRACT OF ANAPHE VENATA LARVA (NOTONDOTIDAE) IN RATS - Bamitale, K. D. S.; Akanmu, M. A.; Ukponmwan, Otas (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Consumption of Anaphe larva had been reported to cause seasonal ataxia and impaired consciousness. Therefore this study examined the neuropharmacological and mechanism(s) of action of aqueous extract of Anaphe venata in rats. Behavioural effects namely rearing, stretching, sniffing and ataxia were determined after the intraperitoneal asministration of aqueous extract of Anaphe larva in rats. Animals were divided into groups and graded doses (100, 200 and 400 mg/kg, i.p.) of extract were administered. The control group was administered normal saline (vehicle). The effects of scopolamine (3 mg/kg, i.p.), flumazenil (2 mg/kg, i.p.), naloxone (2.5 mg/kg, i.p.), and thiamine (1 mg/kg, i.p.) on the observed behavioral changes were also examined. The effects of the extract administered intraperitoneally at a dose of 200 mg/kg on the amphetamine-induced stereotypy and locomotion were evaluated. Aqueous anaphe extract induced significant (p< 0.01) stretching and ataxia behavioural effects while it inhibited rearing behaviour when compared with the vehicle-treated group. However, it had no significant effect on sniffing behaviour. Scopolamine reversed all the effects of the extract on rearing, stretching and ataxia. Both Flumazenil and naloxone only reversed the effects of the extract on stretching and ataxia-induced behaviours significantly. However, thiamine potentiated both stretching and ataxia-induced behaviours. The extract inhibited the amphetamine-induced stereotype behaviour and locomotion. In conclusion, these results showed that these anaphe-induced behavioural effects are mediated via cholinergic, GABAergic, opioidergic and dopaminergic receptor systems with strong muscarinic-cholinergic receptors involvement in ataxia-induced behaviour. We therefore suggest that muscranic-cholinergic like drugs may be of benefit in the management of patients that present with clinical condition of seasonal ataxia.